Prevention of post-contrast kidney injury in patients with cancer - Emanuele Grassedonio; Lorena Incorvaia; Marco Guarneri; Fabio Guagnini; Massimo Midiri (BioExcel Publishing Ltd, 2024)
Post-contrast acute kidney injury is defined as a nephropathy with an increase in serum creatinine of >0.3 mg/dL (or >26.5 μmol/L) or >1.5-times the baseline within 48-72 h of intravascular administration of a contrast medium. Patients with cancer have an increased risk of post-contrast acute kidney injury not only related to the frequent use of contrast medium for computed tomography scans but also to other factors, including the type of tumour, age, oncological therapies, use of other nephrotoxic agents and dehydration. Preventive strategies were developed and may be applied to different risk profiles. Patients at risk may be detected by recently published risk scores.